The Use of Modified High Flow Nasal Cannula (HFNC) In Preterm Infants With Neonatal Respiratory Distress Syndrome (NRSD) In Primary ICU Services - Akhyar Nur Uhud; Arie Utariani; Lucky Andriyanto (Indonesian Journal of Anesthesiology and Reanimation, 2021)
Introduction: NRSD (Neonatal Respiratory Distress Syndrome) is one of the most frequent causes of newborns in intensive care (NICU). Several NICU centers are now using the High Flow Nasal Cannula (HFNC) in recent years. With the use of HFNC as a breath aid in preterm infants, HFNC had the same efficacy ratio as nasal Continuous Positive Airway Pressure (CPAP) (continuous or intermittent). Case Report: A three-day-old baby boy was admitted to anesthesia with respiratory failure due to grade II HMD with suspicion of congenital heart failure. The initial condition showed that a respiratory rate of 70-80x / minute, breathing of the nostrils and retractions in the intercostals and abdomen with 85% post ductal SpO2 with the help of a CPAP mask (Pinsp 10, Fio2 70%). There was a Ronchi sound in the right and left basal lungs, and hemodynamics obtained a pulse of 180-195x / minute, non-invasive blood pressure 95/34 mmHg (54), heart murmurs were not found. During day 1 - day three, the patient uses a CPAP mask until the patient vomits and being consulted to an Anesthesiologist. On day 3 - day seven, the patient uses HFNC; after day seven until day 10, the patient uses neonatal nasal canularis oxygen. Until day 10, the patient is still being treated at the NICU by administering oxygen 0.5 liters/minute with SpO2 ranging from 93-96% with stable conditions but still needing oxygen. Conclusion: The use of Modified High Flow Nasal Cannula (HFNC) in preterm infants with Neonatal Respiratory Distress Syndrome (NRSD) is more effective and efficient than CPAP. The use of HFNC was associated with a lower incidence of nasal trauma and pneumothorax than nasal CPAP.